A giant hydronephrosis disguised as abdominal obesity - Ravishankar Mylaraiah; Nandeesh Venkatappa (Clinical Case Reports, 2024)
Key Clinical Message Abdominal obesity is common in clinical practice. However, it is important to rule out other causes of abdominal distension. We are reporting a case of giant hydronephrosis misdiagnosed as abdominal obesity for a long time.